2020
DOI: 10.1017/s0029665120002736
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Marine Biotoxins in Mussels from Bulgarian coast and Dietary Intake of Different Population Groups

Abstract: AbstractIntroductionLipophilic phycotoxins, produced by toxic phytoplankton species, accumulate in digestive glands of mussels. If contaminated mussels containing marine biotoxins over regulatory levels are consumed, it is assumed that this could result in e.g. gastrointestinal disorders.Objectives Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [ 54 , 55 , 56 ]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [ 57 , 58 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [ 54 , 55 , 56 ]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [ 57 , 58 ].…”
Section: Resultssupporting
confidence: 93%
“…Even if HQs were below the critical value 1, so no possible risks are associated with mussel consumption collected from the study areas, we noted the case of lead which registered the highest calculated HQs from all heavy metals: 0.2 in A1, 0.03 in A3, 0.012 in A2, respectively. Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 91%
“…In addition, the reported levels of DSTs in mussel samples from the Black Sea were far below the regulatory limit [ 24 , 25 ]. Therefore, the risk of significant DSP toxin outbreaks in the northwestern Black Sea is low, as also reported by other authors [ 87 ].…”
Section: Discussionsupporting
confidence: 72%
“…The low levels of YTXs in plankton and previously measured in mussel samples [ 24 , 25 , 87 ], and the reported low oral toxicity of YTX analogues [ 96 , 97 ], suggest a negligible risk of acute intoxication in the western part of the Black Sea. On the other hand, the persistent presence of yessotoxins could result in chronic exposure from shellfish consumption, which might pose a threat to human health [ 98 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation